2019
DOI: 10.1021/acsami.9b06072
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cellulose Nanocrystal-Mediated Conjugated Polymer Aggregation

Abstract: Inducing the self-assembly of π-conjugated polymers into semicrystalline aggregates has been a topic of substantial interest in the field of organic electronics and is typically achieved using energy-intensive solution processing or postfilm deposition methods. Here, we demonstrate the ability of bioderived cellulose nanocrystals (CNCs) to act as structure-directing agents for the conjugated semiconducting polymer, poly­(3-hexylthiophene) (P3HT). CNCs were grafted with polystyrene, P3HT or poly­(N-isopropylacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…To directly attach PPBT onto the surface of the magnetite nanoparticles, a scheme commonly found in the functionalization of carboxylic-containing molecules onto CNCs was used. 24 First, 500 mg of Fe 3 O 4 nanoparticles were dispersed in 60 mL of deionized water with an ultrasonic probe (3 pulses of 30 s each, operated at 50 W, Qsonica Q700 sonicator). The Fe 3 O 4 dispersion was then transferred to a 100 mL round-bottom flask fitted with a magnetic stir bar.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To directly attach PPBT onto the surface of the magnetite nanoparticles, a scheme commonly found in the functionalization of carboxylic-containing molecules onto CNCs was used. 24 First, 500 mg of Fe 3 O 4 nanoparticles were dispersed in 60 mL of deionized water with an ultrasonic probe (3 pulses of 30 s each, operated at 50 W, Qsonica Q700 sonicator). The Fe 3 O 4 dispersion was then transferred to a 100 mL round-bottom flask fitted with a magnetic stir bar.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Hollow silica nanorods with accessible micro‐ and meso‐pores were then subsequently obtained, after calcination of the hybrid nanomaterial. In a completely different area, polystyrene‐ and PNIPAM‐grafted CNC prepared by ATRP were used as structure‐directing agents for poly(3‐hexylthiophene (P3HT), in order to improve the optoelectronic performances of this conjugated semi‐conducting polymer 217 . The presence of the hybrid nanoparticles in P3HT solutions (chloroform) resulted in an increase in P3HT semi‐crystalline aggregate formation, due to unfavorable polymer–polymer interactions at the surface of the CNC, and spatial confinement effects imposed by phase separation.…”
Section: Properties and Applications Of Polymer‐grafted Cnc Obtained By Si‐atrpmentioning
confidence: 99%
“…In a completely different area, polystyreneand PNIPAM-grafted CNC prepared by ATRP were used as structure-directing agents for poly(3-hexylthiophene (P3HT), in order to improve the optoelectronic performances of this conjugated semi-conducting polymer. 217 The presence of the hybrid nanoparticles in P3HT solutions (chloroform) resulted in an increase in P3HT semi-crystalline aggregate formation, due to unfavorable polymer-polymer interactions at the surface of the CNC, and spatial confinement effects imposed by phase separation. The electronic performances of films casted from the P3HT blends were then characterized by organic fieldeffect transistor measurements.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Nevertheless, few attempts have been made with conventional DSC [12,13]. In addition to the pure P3AT systems, crystallization kinetics have also been investigated for blend systems [23,24,25] and block copolymers [26,27,28,29,30,31,32,33]. Müller et al investigated the crystallization of P3HT-polyethylene (PE) diblock copolymer, they found that the crystal growth of P3HT block and PE block remains unaffected: onedimensional for P3HT and spherulitic growth for PE [27].…”
Section: Introductionmentioning
confidence: 99%